Gender Identity Development among Teenagers Living in the Subarctic Region of Russia - Natalia Flotskaya; Svetlana Bulanova; Maria Ponomareva; Nikolay Flotskiy; Tatiana Konopleva (Behavioral Sciences, 2018)
Gender identity is an important element of an individual’s identity and is one of the regulators of human behavior while acquiring social roles. The aim of this empirical research is to study gender identity development among teenagers living in the subarctic territories of Russia. The results show the correlation between types of gender identity among male and female teenagers, the dynamic in the correlation between gender identity types during adolescence and the characteristics of each type of gender identity in adolescence from the point of view of psychological properties.